Exploring the Quality of Eco-Prints from Floral Waste Across Fabric Variations - Aprilia Puteri Ningtarich; Sri Endah Wahyuningsih; Urip Wahyuningsih (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
Textile dyes are commonly used in the production of fashion products. However, to reduce reliance on synthetic textile dyes, the use of natural dyes has become an important alternative. One sustainable method for applying natural dyes is the eco-print technique. This study aimed to examine: (1) the quality of color fastness to soap washing in eco-print results on cotton, linen, and silk fabrics; and (2) the quality of color aging in eco-prints using kenikir flowers on cotton, linen, and silk fabrics. The research employed an experimental method by producing eco-prints on cotton, linen, and silk fabrics. The materials used for eco-printing included kenikir, insulin, grass, and frangipani flowers, applied through a steaming technique. Sample testing was conducted at the UII Textile Laboratory to assess color fastness to soap washing and color aging. Data were analyzed descriptively, based on three repetitions of each test. The findings revealed that the average score for color fastness to soap washing was 4–5, which falls under the good criteria. Meanwhile, the results of the color aging test showed values of 97.66 for cotton, 101.61 for silk, and 114.99 for linen. Among these, silk fabric demonstrated higher results, indicating that the eco-printed motif appeared older or darker in color compared to cotton and linen.